2020
DOI: 10.1101/2020.09.20.305482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dorsal Anterior Cingulate Cortex Encodes the Integrated Incentive Motivational Value of Cognitive Task Performance

Abstract: SummaryHumans can seamlessly combine value signals from diverse motivational incentives, yet it is not well-understood how these signals are “bundled” in the brain to modulate cognitive control. The dorsal anterior cingulate cortex (dACC) is theorized to integrate motivational value dimensions in the service of goal-directed action, though this hypothesis has yet to receive rigorous confirmation. Here, we examine the role of dACC in motivational integration using an experimental paradigm that quantifies combin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 107 publications
(89 reference statements)
0
10
2
Order By: Relevance
“…Toward this end, a coupling between D1DR availability in dorsal striatum and action learning has been found (de Boer et al, 2019). These functions in turn tend to rely on signals of reward (Yee et al, 2021; Yee and Braver, 2018), typically attributed to the mesocorticolimbic DA pathway (Schultz, 1998). Therefore, it is conceivable that the age-related D1DR reductions in these regions might bear specific importance to motivation-based modulation of cognition (De Boer et al, 2017; Westbrook and Braver, 2016; Yee et al, 2021; Yee and Braver, 2018), beyond concomitant changes in structure and metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward this end, a coupling between D1DR availability in dorsal striatum and action learning has been found (de Boer et al, 2019). These functions in turn tend to rely on signals of reward (Yee et al, 2021; Yee and Braver, 2018), typically attributed to the mesocorticolimbic DA pathway (Schultz, 1998). Therefore, it is conceivable that the age-related D1DR reductions in these regions might bear specific importance to motivation-based modulation of cognition (De Boer et al, 2017; Westbrook and Braver, 2016; Yee et al, 2021; Yee and Braver, 2018), beyond concomitant changes in structure and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These functions in turn tend to rely on signals of reward (Yee et al, 2021; Yee and Braver, 2018), typically attributed to the mesocorticolimbic DA pathway (Schultz, 1998). Therefore, it is conceivable that the age-related D1DR reductions in these regions might bear specific importance to motivation-based modulation of cognition (De Boer et al, 2017; Westbrook and Braver, 2016; Yee et al, 2021; Yee and Braver, 2018), beyond concomitant changes in structure and metabolism. The present findings are hence in keeping with neurocognitive theories of aging that attribute losses in cognitive control to deficient DA modulation (Braver and Barch, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when earning rewards during a cognitive control task (e.g., Stroop) is contingent on both speed and accuracy, participants are faster and/or more accurate as potential rewards increase [11,1517]. While studies have examined how motivation to avoid negative outcomes influence cognitive control [1822], a challenge of interpreting these mixed behavioral patterns is that participants deploy a variety of behavioral strategies as potential punishments increase [22,23]. Past work has demonstrated that these strategies, such as increased task processing (e.g., attentional focus) or adjusting decision thresholds, can be linked to different forms of control adjustment (e.g., prioritizing speed versus accuracy; [24–27]).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these data suggested that dACC is critical for processing the emotional content of faces. Previous research in the dACC suggests that this area is important for integrating different dimensions of motivationally-significant stimuli to encode value or emotion 26,27 . Our findings further support this view, suggesting dACC may play a role in integrating valence and intensity components of emotion during affective and salience processing.…”
Section: Discussionmentioning
confidence: 99%